Synthesis and characterization of optical properties of barium titanate (BaTiO3) with the addition of moringa, banana, matoa, and ketapang leaves extracts - Dewi, Rahmi; Apriwandi, Apriwandi; Hamzah, Yanuar; Sari, Eza Tirta; Butarbutar, Kheny Kernila; Putri, Nadja Melika; Nathania, Nazhiwa; Aritonang, Surya Ardika; Hartini, Titin; Hayati, Fitri; Maslyah, Maharani Nur; Sawitri, Seli Novalin; Komariah, Siti; Nursyahara, Septia; Nuraini, Nasywa; Aisy, Rihla Datul; Safira, Putri; Rusmanianty, Rusmanianty; Pratiwi, Dinda; Adela, Adela; Pasaribu, Veny Sriulina; Azhara, Vina Naomi; Febrita, Ayang (Universitas Riau, 2025)
Environmentally friendly synthesis of barium titanate (BaTiO3) nanoparticles was conducted using natural leaf extracts of Moringa oleifera, Musa spp., Pometia pinnata, and Terminalia catappa as green dopants via the sol-gel method. This study aims to evaluate the influence of different leaf extracts on the optical properties of BaTiO3 characterized by UV-Vis spectroscopy. Each sample exhibited distinct absorption spectra, reflecting variations in phytochemical composition among the extracts. The results showed that Terminalia catappa and Pometia pinnata extracts produced the highest band gap values, 3.36 eV and 3.35 eV respectively, indicating optical activity in the ultraviolet region. Musa spp. extract resulted in a band gap of 2.81 eV, while Moringa oleifera extract yielded the lowest value of 2.59 eV. These differences suggest that the type of plant extract significantly affects the optical characteristics of the synthesized BaTiO3. This research highlights the potential use of local biomass in the development of functional BaTiO3-based materials through green synthesis approaches.